Energy management and environmental aspects of a high capacity perlite furnace through exergetic analysis - Gurturk, Mert; Öztop, Hakan Fehmi; Hepbasli, Arif (Pergamon-Elsevier Science Ltd, 2014)
Utilization opportunities of perlite have made the product adaptable to numerous applications in the construction, industrial, chemical, horticultural and petrochemical industries. In this paper, exergetic assessment of a High Capacity Perlite Furnace (HCPF) used in a perlite expansion process was performed. The furnace is vertical, partially insulated and has a high pertlite production capacity. Both energy and exergy relations were derived for the considered the HCPF. Some parameters, such as losses, irreversibility and design, were considered for determining energy and exergy efficiencies. The obtained results were compared with various perlite expansion furnaces in the literature. The energy and exergy efficiency values for the HCPF were calculated to be 69% and 37%, respectively. The results were also assessed in terms of energy management for the perlite production, economic evaluation of the HCPF and environmental aspects. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Exergy; Thermodynamics; Perlite; Perlite expansion furnace; Furnace